Bone density in competitive figure skaters - Oleson, C. V.; Busconi, B. D.; Baran, D. T. (Archives of Physical Medicine and Rehabilitation, 2002)
OBJECTIVES: To compare the bone mineral density (BMD) of competitive female teenage figure skaters with a history of fracture with the BMD of skaters without fracture and to compare each group to age-matched, nonathletic controls. DESIGN: Retrospective age-matched cohort. SETTING: Tertiary care medical center and 3 local skating clubs. PARTICIPANTS: Thirty-six adolescent female competitive skaters (10 with fracture, 26 without fracture) to 22 age-matched controls. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: BMD was estimated by quantitative ultrasound. RESULTS: Skaters who had suffered stress fractures had BMD values comparable with those of healthy nonathletic controls. However, skaters who had not suffered stress fractures had calcaneal BMD values 15% to 24% greater than either the controls or skaters with fractures. Among the skaters without fracture, there was a 14% to 19% higher calcaneal BMD in skaters who executed triple jumps relative to skaters who performed only double jumps. Furthermore, there was 7% to 11% greater BMD in the landing foot of the skaters relative to the takeoff foot. CONCLUSIONS: Stress fractures in adolescent skaters are not caused by low bone mass but may result from excessive forces placed on a normal skeleton. Our findings also support the hypothesis that higher peak forces are applied to the landing foot relative to the takeoff foot.